Jousting with Straw Men Comment on Westen, Novotny, and Thompson-Brenner (2004). [article]. - Weisz, John R.
Empiricall supported treatments (ESTs) do not cure every patient, and the randomized trial is not a flawless methodology. Upon these often-noted and widely accepted points, D. Westen, C. M. Novotny, and H. Thompson-Brenner (2004) built a critique of ESTs and EST research. However, important workdeveloping effective, clinically relevant treatments for serious problem was omitted from the Westen et al. (2004) review. Little documentationwas offered for the purported "assumptions " of EST methodology that Westen et al (2004a) criticized, and different review standards were applied to studies supporting versus those disagreeing with Westen et al.'s (2004a) views. Finally, the correlational reserach designs.proposed as a remedy by Weten et al.(2004a) have far more serious weaknesses than ramdomized trials, thoughtfully applied to real world clinical care. -- ( from the author)